2024
DOI: 10.1371/journal.pone.0301932
|View full text |Cite
|
Sign up to set email alerts
|

Neurodiversity and cognitive load in online learning: A focus group study

Anne-Laure Le Cunff,
Vincent Giampietro,
Eleanor Dommett

Abstract: It is widely accepted that cognitive load plays a crucial role in online learning. However, despite neurodevelopmental conditions being the largest category of qualifying disabilities in education, and the rise of online learning, there is little understanding of the factors impacting cognitive load in online learning for neurodivergent students and how these factors differ from those affecting neurotypical students. This study used qualitative comparison groups with neurotypical and neurodivergent students to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 83 publications
1
1
0
Order By: Relevance
“…Our main finding is that neurodivergent students reported significantly more extraneous cognitive load (ECL) in online learning than neurotypical students, which partly supports hypothesis H1. This result corroborates the findings of a previously conducted focus group study, where the qualitative analysis suggested higher perceived ECL for neurodivergent students in online learning [53].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our main finding is that neurodivergent students reported significantly more extraneous cognitive load (ECL) in online learning than neurotypical students, which partly supports hypothesis H1. This result corroborates the findings of a previously conducted focus group study, where the qualitative analysis suggested higher perceived ECL for neurodivergent students in online learning [53].…”
Section: Discussionsupporting
confidence: 91%
“…The few studies that did include neurodivergent participants found that attention, linguistic complexity, and content redundancy may impact cognitive load in online learning for this population [52]. Furthermore, a focus group study found that neurodivergent students face specific challenges in managing their cognitive load during online learning, particularly in domains such as listening, writing, and decision making [53]. However, no large-scale quantitative study has to our knowledge investigated the relationship between neurodiversity and cognitive load in online learning.…”
Section: Introductionmentioning
confidence: 99%